Let's solve each equation step by step.
-
Solve for x in:
\( 5x - 3 - x = 21 \)
Combine like terms:
\( 4x - 3 = 21 \)
Add 3 to both sides:
\( 4x = 24 \)
Divide by 4:
\( x = 6 \)Answer: \( x = 6 \)
-
Solve the equation:
\( 7x - 3 - 4x = 9 \)
Combine like terms:
\( 3x - 3 = 9 \)
Add 3 to both sides:
\( 3x = 12 \)
Divide by 3:
\( x = 4 \)Answer: \( x = 4 \)
-
What value of x makes the statement true?
\( 6x - 8 = 2x + 4 \)
Move 2x to the left:
\( 6x - 2x - 8 = 4 \)
Combine like terms:
\( 4x - 8 = 4 \)
Add 8 to both sides:
\( 4x = 12 \)
Divide by 4:
\( x = 3 \)Answer: \( x = 3 \)
-
Solve for x:
\( 5(-2x + 4) = 40 \)
Distribute 5:
\( -10x + 20 = 40 \)
Subtract 20 from both sides:
\( -10x = 20 \)
Divide by -10:
\( x = -2 \)Answer: \( x = -2 \)
To summarize the answers:
- \( x = 6 \)
- \( x = 4 \)
- \( x = 3 \)
- \( x = -2 \)